2000
DOI: 10.15760/etd.895
|View full text |Cite
|
Sign up to set email alerts
|

The Crossover Effects of Supervisor Work-Family Positive Spillover on Employee Sleep Deficiency: Moderating Effects of Family Supportive Supervisor Behaviors (FSSB)

Abstract: The majority of literature on the work-family interface has focused on, and provided evidence of, the conflict associated with engagement in both work and family roles (Eby, Casper, Lockwood, Bordeaux, & Brinley, 2005). Research examining the positive aspects of work and family participation remains limited. The current study investigated how work-family positive spillover is transferred between members of the supervisoremployee dyad and subsequently how this affects employee sleep outcomes. It was hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 294 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Drawing on Conservation of Resource theory (COR), Crain (2012) applied FSSB to employees' physical research, and found out that FSSB moderated the association between supervisor positives pill over and employee sleep duration [7]. Samantha and Jonathon (2013) collect data from 628 employees of a health system, using path analytic tests of moderated mediation, provide support for the mediated effect of family-supportive climate on employee work-family conflict (through family supportive supervisor behaviors) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on Conservation of Resource theory (COR), Crain (2012) applied FSSB to employees' physical research, and found out that FSSB moderated the association between supervisor positives pill over and employee sleep duration [7]. Samantha and Jonathon (2013) collect data from 628 employees of a health system, using path analytic tests of moderated mediation, provide support for the mediated effect of family-supportive climate on employee work-family conflict (through family supportive supervisor behaviors) [8].…”
Section: Introductionmentioning
confidence: 99%